Beam steering flexible transparent metasurfaces based on multi-bit phase gradient variations - Meijia Guo; Penghui Xin; Haoyuan Sun; Hengfeng Li; Leonid F. Chernogor; Zhejun Jin; Tian Liu; Yu Zheng (Scientific Reports)
Abstract In this study, a coded metasurface design employing the Pancharatnam–Berry (PB) phase principle was proposed, with precise beam steering achieved via phase gradient variations. The designed metasurfaces have the characteristics of flexibility and transparency. The metasurface unit uses a modified C structure to form dual-resonant points to form a wide frequency band, and the PB phase satisfy the relationship between the rotation angle of the element and the double difference of the reflected phase, by encoding metasurface arrays, functions such as reducing linearly polarized radar cross sections (RCS) and steering circularly polarized beams can be achieved. The array effectively reduces the linear polarization RCS in the 13–20 GHz band by rotating the phase difference between the unit metasurfaces. Under circularly polarized plane wave excitation, the metasurface unit achieves a high polarization conversion ratio (PCR) of approximately 0.9 within the 14–25 GHz frequency band. Experimental results show that the metasurface array achieves ± 50° wide-angle beam steering along both X- and Y-axes while maintaining 82% visible-light transmittance, providing potential applications in flexible electronics and reconfigurable intelligent surfaces (RIS).